2020
DOI: 10.3390/cells9102289
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Mitochondrial Dysregulation Caused by α-Synuclein in Dictyostelium discoideum

Abstract: Alpha synuclein has been linked to both sporadic and familial forms of Parkinson’s disease (PD) and is the most abundant protein in Lewy bodies a hallmark of Parkinson’s disease. The function of this protein and the molecular mechanisms underlying its toxicity are still unclear, but many studies have suggested that the mechanism of α-synuclein toxicity involves alterations to mitochondrial function. Here we expressed human α-synuclein and two PD-causing α-synuclein mutant proteins (with a point mutation, A53T,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 89 publications
8
26
0
Order By: Relevance
“…In otherwise unstressed cells, we found that DJ-1 knockdown caused an elevation of mitochondrial respiration [18] (Figure 1). Similar mitochondrial hyperactivity was recently reported in Dictyostelium cells overexpressing the wild type or PD-associated mutant forms of α-synuclein [58], in cultured human neuroblastoma cells treated with exogeneous α-synuclein [59], in lymphoblasts from idiopathic PD patients [28] and in fibroblasts from genetic PD patients with Parkin mutations [29]. This raises the intriguing possibility that mitochondrial hyperactivity is an initiating event in these different types of PD.…”
supporting
confidence: 80%
“…In otherwise unstressed cells, we found that DJ-1 knockdown caused an elevation of mitochondrial respiration [18] (Figure 1). Similar mitochondrial hyperactivity was recently reported in Dictyostelium cells overexpressing the wild type or PD-associated mutant forms of α-synuclein [58], in cultured human neuroblastoma cells treated with exogeneous α-synuclein [59], in lymphoblasts from idiopathic PD patients [28] and in fibroblasts from genetic PD patients with Parkin mutations [29]. This raises the intriguing possibility that mitochondrial hyperactivity is an initiating event in these different types of PD.…”
supporting
confidence: 80%
“…Another of the phenotypes in which coexpression of tau and α-synuclein had opposing effects was in mitochondrial respiratory function. Previously we showed that α-synuclein did not cause an impairment in mitochondrial function but instead it increased respiratory activity coordinately in all components measured (Fernando et al, 2020). This result was consistent with increases in mitochondrial respiration seen in lymphoblast cell lines made from iPD patients (Annesley et al, 2016), fibroblasts from iPD patients (Haylett et al, 2016) and when neuroblastoma cells were seeded with α-synuclein fibrils (Ugalde et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Tau was detected using an anti-tau antibody coupled with Alexa-Fluor 594-conjugated secondary antibody and was seen throughout the cytoplasm of the cell. α-synuclein had previously been seen to localise to the cortex of the cell in D. discoideum (Fernando et al, 2020). To detect α-synuclein and tau in the cotranformants anti-tau and anti-α-synuclein antibodies were coupled with Alexa-Fluor 594 and 488-conjugated secondary antibodies respectively.…”
Section: Tau Is Localised Throughout the Cytoplasm In D Discoideum Whereas α-Synuclein Is Localised To The Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated respiration was accompanied by an elevated ATP steady state and elevated ROS production [ 72 ]. Since that publication, the findings have been confirmed in LCLs from a larger cohort of idiopathic PD patients (unpublished data) and in other cellular PD models, including exposure of the neuroblastoma cell line SH–SY5Y to fibrillar alpha–synuclein [ 73 ] and in the simple eukaryotic model Dictyostelium discoideum , expressing genetically manipulated PD-associated genes, including α-synuclein [ 74 ] and DJ-1 [ 75 ]. In all cases, mitochondrial respiration was increased, not decreased.…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 93%